Regional measurement and dynamic evolution of the development level of China's digital economy - Wang, Wentao (Frontiers in Environmental Economics, 2024)
In the wave of digital transformation, digital economy, as one of the core growth poles of the national economy, which is becoming a new driving force to promote economic development. In view of the problem of the unbalanced development of China's digital economy, and to construct an indicator system for the level of digital economic development. The study is based on the panel data of 30 provinces (Tibet is not included in the study due to missing data) from 2013 to 2021, and comprehensively utilizes the entropy method, the Tyrell index and the Moran index method, the regional level of China's digital economic development is measured. And based on this, it further reveals the regional differences in China's digital economic development and the dynamic evolution characteristics of source and distribution. The purpose of this study is to provide practical experience and effective measures for promoting the coordinated development of digital economy in various regions and narrowing the regional digital divide. The study shows that the level of China's digital economy development has been increasing, and the digital economy has become the main engine of national economic development. The development of China's digital economy shows significant positive spatial dependence, spatial agglomeration and regional imbalance, and the development of the digital economy faces the problem of digital divide. The regional differences in the level of China's digital economy development are mainly due to inter-regional differences, and there is a trend of gradual reduction. There is also a certain degree of ups and downs in the process of regional digital economy development, and its spatial heterogeneity and convergence characteristics need to be further studied.